Thinking about indignation - Belmonte García, Olga (Razón y fe, 2018)
The indignation is becoming fashionable. What is it hidden? What is behind this concept? Is it a mere indication of our current problems or does it go beyond that? It certainly means more than what it seems and what it demands; seen merely as a coherent behavior with a positive and transformative vision of the reality. This and a lot more is brought out into the open in this short text.
Keywords: indignation; resistance; commitment; social change and open society